The Influence of Augmented Reality-Based Learning Media on the Understanding of Mathematical Concepts in Elementary School Children - Berta Apriza; Irawan Suprapto; Yasinta Mahendra (West Science Interdisciplinary Studies, 2024)
This research investigates the impact of Augmented Reality (AR) based learning media on the understanding of mathematical concepts among primary school children. Employing a literature review method, the study outlines recent findings in literature concerning the application of AR in mathematics education. The results indicate that the use of AR can enhance motivation, active participation, and the understanding of mathematical concepts among primary school children. AR's ability to present material in a more concrete and applicable form has a positive impact on the understanding of concepts that are often challenging for students at their cognitive development level. Despite challenges in implementation and infrastructure development, this research provides a foundation for the integration of AR in mathematics education in primary schools. It is recommended that the implementation of AR be carefully considered in the primary school mathematics curriculum with adequate teacher training and appropriate infrastructure investment.